LEGAL CLINIC AS A FACTOR OF LAWYER’S EMOTIONAL INTELLIGENCE AND PROFESSIONAL ETHICS DEVELOPMENT - M. Kuchuk, Andrii; I. Andrusyshyn, Bohdan; V. Bilozorov, Yevhen; V. Minchenko, Olha; A. Filianina, Liudmyla (Revista Gênero e Interdisciplinaridade, 2020)
The urgency of the research is stipulated by the necessity to critically reflect on functioning of an innovative form of legal education – a legal clinic in order to determine the possibility of clinical education to be a factor in the development of students’ emotional intelligence and professional ethics. The purpose of the article is to systematically cover the possible positive and negative aspects of the widespread introduction of legal clinic as a means of individual students’ qualities development into law education. The study is based on the method of systematic analysis, allowing comprehensively cover legal clinics functions and critically evaluate the impact of legal clinics on emotional intelligence and professional ethics of future lawyers’ development. The article shows that legal clinic, being an innovative form of legal education aimed at developing practical skills of future lawyers, performs both educational and social functions. Legal clinic promotes the development of emotional intelligence (allowing students to better understand and control their emotion, as well as to adequately perceive the client’s psychological state, choosing appropriate tactics of behavior) and professional ethics (understanding the importance of the principle of the rule of law, the priority of human rights, awareness of the role of a lawyer in society and the importance of pro bono activities). Article materials can be used for further study of legal clinics impact on the future law practitioners’ individual qualities development, and can also be the benchmarks for improving the legal clinical education.